Efficacy and safety of fondaparinux in preventing venous thromboembolism in Chinese cancer patients: a single-arm, multicenter, retrospective study - Wang, Lei; Su, Zhong; Xie, Chunying; Li, Ruijun; Pan, Wei; Xu, Lu; Chen, Fei; Cheng, Gang (Frontiers in Oncology, 2023)
Objective: Fondaparinux is a synthetic anticoagulant for the prevention of venous thromboembolism (VTE), while its administration in Chinese cancer patients is rarely reported. This study aimed to assess the efficacy and safety of fondaparinux in preventing VTE in Chinese cancer patients. Methods: A total of 224 cancer patients who received fondaparinux treatment were reviewed in this single-arm, multicenter, retrospective study. Meanwhile, VTE, bleeding, death, and adverse events of those patients in hospital and at one month after treatment (M1) were retrieved, respectively. Results: The in-hospital VTE rate was 0.45% and there was no (0.00%) VTE occurrence at M1. The in-hospital bleeding rate was 2.68%, among which the major bleeding rate was 2.23% and the minor bleeding rate was 0.45%. Moreover, the bleeding rate at M1 was 0.90%, among which the major and minor bleeding rates both were 0.45%. The in-hospital death rate was 0.45% and the death rate at M1 was 0.90%. Furthermore, the total rate of adverse events was 14.73%, including nausea and vomiting (3.13%), gastrointestinal reactions (2.23%), reduced white blood cells (1.34%), etc. Conclusion: Fondaparinux could effectively prevent VTE with low bleeding risk and acceptable tolerance in cancer patients.